A review of clean-label approaches to chilli paste processing - Jamaluddin, Faathirah; Mohd Adzahan, Noranizan; Mohamad Azman, Ezzat; Mohamad, Azizah; Yusof, Noor Liyana; Sulaiman, Alifdalino (Wiley-Blackwell, 2021)
Consumer demand for clean-label food products is increasing. Moreover, the production of ready-to-cook products have begun to include clean-label efforts. Dried chilli, the raw material for chilli paste, is susceptible to contaminants such as mould dirt and pesticides that must be removed to maintain the safety and quality of products. In this review, trends related to processes involved in chilli paste production are highlighted. Improvements in preservation technology and the potential for using a clean-label approach to produce premium-quality chilli pastes were explored. Ultrasound washing and high-pressure processing could be combined as part of a hurdle technique for processing chilli pastes that align with consumer values. Ultrasound washing disinfects and removes dirt pesticides and chemical residues present on dried chillies. High-pressure treatments inactivate microorganisms and enzymes, which could extend the shelf-life of chilli pastes. Additionally, organic acid and garlic can be used as natural preservatives to improve the formulation without using artificial ingredients. This clean-label concept can be integrated into the hurdle strategy to produce chilli paste that fulfils the consumer demand for a safe, naturally nutritional product with an extended shelf-life.